Willingness to be vaccinated against COVID-19: the role of risk perception, trust in institutions, and affects - Ghozlane Fleury-Bahi; Arnaud Sapin; Oscar Navarro; Abdel Halim Boudoukha; Jean-Michel Galharret; Amélie Bret; Anne Congard (Frontiers in Psychology, 2023)
IntroductionVaccination is one of the most effective ways to stop the COVID-19 pandemic and prevent severe disease. This study aims to ascertain the determinants of COVID-19 vaccination acceptance in the French population before the vaccine was introduced (France’s second lockdown) and during the roll-out of the vaccination campaign (France’s third lockdown). We focus on the following as determinants of willingness to be vaccinated: risk perception, affects related to the risk, and trust in political and health institutions.MethodThe study was conducted among two convenient samples including 591 and 474 participants. The results show that the timing of the crisis was important. While the intention to be vaccinated was relatively low before the vaccines were introduced, it became significantly higher when the vaccination campaign was deployed.ResultsThe results show that risk perception and trust in health institutions are the most relevant predictors of intention to be vaccinated.DiscussionResults are discussed in terms of the effectiveness of communication campaigns.